Paradigma Holistic Education - Sayfullah, Hasan (Edukais : Jurnal Pemikiran Keislaman, 2018)
The ever-expanding rotation of science, along with the remarkable progress of civilization and human science in this modern age, has arisen multidimensional and multi-complex human life problems and crises, such as: ecological crisis, humanitarian crisis , moral crises (demoralisation), greater social and economic inequality, violence and crime, and other crises. The occurrence of that is because of the enormous inequality between science and technology that developed so rapidly with moral wisdom and humanity that is not developed at all, if not said backwards. Furthermore, if traced the root cause, as a result of the unsuitability between the demands of the times with the world view of the modern world. On the one hand, the flow of globalization has eliminated human relationships in a more open, dialogical, tolerant, and plural climate. The most dominant significance of character change, mindset, attitude, ethics, and morals is endorsed in educational institutions. So when there is a deterioration and anxiety in human life that is definitely blamed is the educational institution. However, on the other hand, the worldview adopted by most modern humans does not allow the dialogical and humanist relations to grow and develop. Based on the concept of holistic education is an offer.